2007
DOI: 10.1002/mar.20157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of knowledge types on consumer‐perceived risk and adoption of genetically modified foods

Abstract: Scientists have asserted that genetically modified (GM) food offers financial, environmental, health, and quality benefits to society, but the realization of such benefits depends on consumer acceptance of this new technology. Consumer concerns about GM food raise questions about what consumers know about GM food and to what extent this knowledge translates into their evaluations of GM products. The present research empirically examines the effect of both objective and subjective knowledge on perceived risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
5
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 48 publications
6
190
5
3
Order By: Relevance
“…The results for H6 are inconsistent with the research done by Klerck and Sweeney (2007) [6], which stated that the perceived risk will affect consumer purchase behaviors and decisions. This difference in results may be because the researchers conducted their investigations in different industries.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…The results for H6 are inconsistent with the research done by Klerck and Sweeney (2007) [6], which stated that the perceived risk will affect consumer purchase behaviors and decisions. This difference in results may be because the researchers conducted their investigations in different industries.…”
Section: Discussioncontrasting
confidence: 92%
“…The empirical results for H3 (Better product knowledge via hydrogen-electric motorcycles will have a significant and negative influence on consumers' purchase intentions owing to the perceived risk) are consistent with those obtained by Klerck and Sweeney (2007) [6]. Both subjective and objective knowledge of a product result in the perceived risk for consumers.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In a study on consumer consumption of genetically modified food, Klerck and Sweeney (2007) found that subjective knowledge reduces psychological risk of the technology, which further influences the propensity to search for and buy genetically modified foods. After initial trial of a new technology, consumers can become more self-confident and knowledgeable about the technology, and continuing to use it enhances their self-concept of being knowledgeable.…”
Section: H5 Personal Innovativeness Positively Influences Continuancmentioning
confidence: 99%